The Pricing Journey The Organizational Transformation Toward Pricing Excellence - Liozu, Stephan (Stanford University Press, 2015)
Innovations in pricing can be transformative, but to reach their potential companies must devote equal attention to technical and organizational capabilities. Most firms, however, only pay attention to the technical dimensions of pricing, which severely limits the success of their initiatives. To remedy this, The Pricing Journey provides an integrated guide to the organizational, social, and behavioral aspects of pricing-drawing on principles of socio-technical change. Based on extensive qualitative and quantitative research in an array of firms around the world, Stephan M. Liozu provides a practical roadmap for management teams that aim to reach a new level of pricing power.Liozu introduces the 5 C model of transformation, which relies on change, capabilities, champions, confidence, and center-led organizational design to create effective and lasting pricing strategies. Rooting his recommendations in research and practice, Liozu proposes specific capabilities to develop on the road to pricing excellence. This book prepares pricing and marketing professionals to be true strategic partners, while contributing the study of pricing transformation